Exploring the Impact of Lesson Study as a Collaborative Teaching Strategy in Higher Education - Kundariati, Maisuna; Susilo, Herawati; Balqis, Balqis; Setiowati, Frida Kunthi; Masita, Rahmi (Journal of Learning Improvement and Lesson Study, 2023)
Lesson study is a class-based & collaborative continuous teacher professional development strategy to optimize student learning services. The aim of this study was to determine the impact of lesson study on improving the quality of learning in higher education. This research is a mix method research, which was conducted for one semester. Learning is carried out in a hybrid way in the odd semester of the 2021/2022 academic year in six plant physiology classes using Problem-based Learning (PBL). The research subjects consisted of biology education students and undergraduate biology students at the Universitas Negeri Malang. The research instruments include chapter design, lesson design, lesson plans, lesson study observation sheets, essay tests on cognitive learning outcomes. Lesson study is carried out in three stages, namely plan, do, and see. The results showed that the learning designed and implemented with lesson study showed an improvement in each meeting. Improvements in learning can occur because educators and observers reflect on learning activities.